Overview of Characteristics, Resilience and Psychological Well-Being in PMI Volunteers in Pekalongan - Kusumaningrum, Rosi; Nafiah, Hana (Jurnal Multidisiplin Indonesia, 2024)
Being a volunteer is a very real act of humanity. Many people are interested in volunteering, but they do not know the impact of the service duties of a volunteer who is prone to experiencing physical and psychological problems such as fatigue, discomfort, and helplessness caused by high-intensity work, fear and anxiety for patients and family members. This study aims to find out the description of characteristics, resilience and PWB in PMI volunteers. This research method uses quantitative descriptive. Data collection uses total sampling. The sample in this study is PMI Volunteers in Pekalongan. Respondents' resilience was measured using the Resilience Scale (RS-14) questionnaire. As for PWB, it was measured using the Ryff Scales of Psychologigal Well Being questionnaire. The data analysis used is the value of frequency distribution, mean, median and standard deviation. The results of the study showed that the average respondent was 27 years old (SD=5.16). The average length of time to join PMI Pekalongan volunteer members is 4 years (SD=2.37). Most of the respondents were male as many as 42 (67%). As many as (51%) respondents have a high school education. Of the 63 respondents, all (100%) have registered membership status and more than half of the respondents are still actively working (78%). Of the 63 respondents, as many as 32 (51.8%) respondents had a low level of resilience. And as many as 32 (51.8%) respondents have a high level of PWB. The conclusion of this study states that the decrease or increase in the level of resilience, psychological well-being is influenced by several factors. Psychiatric nurses are expected to provide interventions that can increase the level of resilience and psychological well-being.